Pandemic, Quarantine, and Psychological Time - Grondin, Simon; Mendoza-Duran, Esteban; Rioux, Pier-Alexandre (Frontiers in Psychology, 2020)
This article addresses the feeling of strangeness about the perception of time that many people with ordinary lifestyles experienced during the quarantine imposed to fight the presence of Covid-19. It describes different aspects of psychological time affected by the interruption of a normal routine and suggests some cognitive mechanisms, attention and memory, that might have been at play, leading to perceive time as being more or less long. The article also describes the critical role of anxiety and temporal uncertainty and how they may affect the functioning of an internal clock, and reminds the reader that there are individual differences in time-related aspects of the personality that contribute to the variety of impressions about duration experienced during the quarantine.